The Effectiveness of Emotion Regulation Training on Frustration Tolerance and Executive Functions in Adolescents of Tehran City - Etaati, Zahra; Ghorbani, Nowzar; Alipanah, Shahin; Haghighat Bayan, Nazanin; Rezaei, Sara (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: The present study aimed to investigate the effectiveness of emotion regulation training on frustration tolerance and executive functions among adolescents in Tehran City.Methods and Materials: The research method was quasi-experimental with a pretest–posttest design including a control group. The statistical population comprised all secondary school adolescents in Tehran during 2025, from which 30 participants were selected through convenience sampling and randomly assigned to experimental and control groups. The experimental group participated in ten 90-minute sessions of emotion regulation training, whereas the control group received no intervention. To assess the study variables, the Harrington Frustration Tolerance Questionnaire (2005) and the Barkley Deficits in Executive Functioning Scale (2011) were used.Findings: Findings indicated that emotion regulation training led to a significant increase in frustration tolerance and improvement in executive functions—including inhibitory control, cognitive flexibility, and self-regulation—in the experimental group (p < .05).Conclusion: These results suggest that emotion regulation training can effectively enhance cognitive and emotional resilience in adolescents by improving self-awareness, emotional management, and flexible thinking skills. Therefore, implementing such training programs in educational and counseling settings is recommended to promote mental health and executive functioning among adolescents.Keywords: Emotion Regulation Training, Frustration Tolerance, Executive Functions, Adolescents